Quercus ilex as bio-indicator of metal pollution in the area of the Terni, Italy. (1st May 2019) - Gratani, Loretta; Crescente, Maria Fiore; Catoni, Rosangela; Guiducci, Ilaria Rita; Bartoli, Donatella; Piccini, Gaia; Luigi, Romina Quondam; Rocchi, Federica; Varone, Laura
Trees are effective scavengers of both gaseous and particulate pollutants from the atmosphere. The objective of this research was to evaluate heavy metal pollution in the territory of the steel factory 'Acciai Speciali Terni S.p.A' (Italy) by monitoring Quercus ilex trees naturally growing in the area. Measurements were carried out at three sites (site 1, 2 and 3) at different distances from the steel factory (1.9, 2.3 and 7.2 km from the factory, respectively). The most part of the metals (As, Ba, Cd, Cr, Fe, Ni, Pb, V and Zn) had a decreasing trend from site 1 to site 3. Among them, Cr showed the highest decrease (97%) and Zn the lowest (44%). At a morphological level, leaf mass area (LMA) was lower at site 3 (12.9±1.0 mg cm ‒2 ) than at site 1 (14.9±1.1 mg cm ‒2 ). The same trend was observed for leaf thickness significantly decreasing by 38% from site 1 to site 3. Overall, the results highlighted a high responsiveness of Q. ilex, making it a good bio-indicator for the long-term monitoring of metal concentration variations in the territory of the steel factory.